MODEL PERUMUSAN KEBIJAKAN LUAR NEGERI INDONESIA DALAM MENJADI ANGGOTA INDEPENDENT AUDIT ADVISORY COMMITTEE (IAAC) PERIODE 2020-2022 - Grace Nainggolan; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Indonesia has potential and achievement in the field of auditing until the Audit Board using the opportunity to become the member of Independent Audit Advisory Committee (IAAC) in United Nations (UN) period of 2020-2022. Nomination of Dr. Agus Joko Pramono, S.ST, M.Acc, Ak., CA., CSFA., CPA. as a member of the committee is considered to have quality human resources. This research uses the perspective of neo-realism, theory of decision-making by Graham T. Allison and the analysis level of the nation state. The research method used was descriptive qualitative research by collecting the data in the form of documentary study during the internship at Ministry of Foreign Affairs in the process of nominating Indonesia becoming IAAC member, library research, and some UN journals, and official website of BPK or Ministry of foreign affairs, books, and other supporting websites. The formulation model of Indonesia foreign policy in becoming a committee member was the organization process, where the result of organization decision was obtained through the procedure stages and mechanism stages in accordance with the Standard Operating Procedure (SOP) and Term of Reference (TOR). The procedure stages consist of recruiting members based on Equitable Geographical Representation (EGR), candidate qualifications and personal practice, as well as internal and external support. The mechanism stages consist of campaign and obtaining endorsement from the Chair of the Asia Pacific and UN Committee V. Keywords: Organizational Process Model, Foreign Policy, Committee Member.